2010
DOI: 10.1002/hbm.20971
|View full text |Cite
|
Sign up to set email alerts
|

Whole brain‐based analysis of regional white matter tract alterations in rare motor neuron diseases by diffusion tensor imaging

Abstract: Different motor neuron disorders (MNDs) are mainly defined by the clinical presentation based on the predominance of upper or lower motor neuron impairment and the course of the disease. Magnetic resonance imaging (MRI) mostly serves as a tool to exclude other pathologies, but novel approaches such as diffusion tensor imaging (DTI) have begun to add information on the underlying pathophysiological processes of these disorders in vivo. The present study was designed to investigate three different rare MNDs, i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
101
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(112 citation statements)
references
References 54 publications
(59 reference statements)
7
101
1
Order By: Relevance
“…One previous application of DTI in motor neuron diseases included 24 pure HSP patients and reported significant alterations in motor pathways and projections to the limbic system and corpus callosum (20). In our analysis, patients with HSP-TCC had additional widespread alterations in other areas, including the brain stem, cerebellum and anterior thalamic radiations, thalami, superior longitudinal fasciculi, uncinate fasciculi, and sagittal stratum.…”
Section: Discussionmentioning
confidence: 58%
“…One previous application of DTI in motor neuron diseases included 24 pure HSP patients and reported significant alterations in motor pathways and projections to the limbic system and corpus callosum (20). In our analysis, patients with HSP-TCC had additional widespread alterations in other areas, including the brain stem, cerebellum and anterior thalamic radiations, thalami, superior longitudinal fasciculi, uncinate fasciculi, and sagittal stratum.…”
Section: Discussionmentioning
confidence: 58%
“…37 DTI studies of patients with hereditary spastic paraparesis have also demonstrated prominent posterior CC involvement, notably not detected in the LMN-only slowly progressive disorder (ie, X-linked spinobulbar muscular atrophy). 57 It has been reported that in ALS and PLS, there is a loss or shrinkage of Betz cells in the premotor cortex, but the cortical motor neurons seem to degenerate more in PLS than ALS. 58 Therefore, all these findings together support the hypothesis that the T1 MTC hyperintense signal intensity, when present, expresses a distinct ALS phenotype characterized by a more severe cortical motor neuron degeneration, with a more prominent "dying back" degeneration of neurons of the CST.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, magnetic resonance imaging (MRI) studies using voxel-based morphometry (VBM) and diffusion tensor imaging (DTI) reported widespread white matter and subtle gray matter changes in the frontal regions [40]. Further research [41] found widespread white matter changes in the corticospinal tract and in the limbic system, while another study [42] described multifocal white matter changes, mainly in the brainstem. A recent positron emission tomography (PET) [43] study also identified hypometabolism in the frontal regions, in ten patients with SBMA.…”
Section: Clinical Featuresmentioning
confidence: 99%